Health technology assessment in musculoskeletal care: A narrative review of evolving methodologies, clinical evidence, and research gaps - Vinh, Nguyen Huu (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2025)
Introduction: Health Technology Assessment (HTA) is a systematic, evidence-based process for evaluating healthcare technologies and guiding resource allocation. It plays a vital role in clinical decision-making and hospital management, especially in Musculoskeletal (MSK) medicine, ensuring interventions are appropriate, effective, and cost-efficient. Methods: This review applies the EUnetHTA Core Model® version 3.0, which standardizes assessments across nine domains, including safety, effectiveness, economics, and ethics. Rapid HTA approaches are also examined to highlight methodological diversity. Data on achievements and research gaps were synthesized from evaluations of advanced diagnostic systems (e.g., EOSedge™) and digital health tools (e.g., telemedicine). Results: HTA has enabled safer, higher-quality technology adoption. The EOSedge system achieved 3 - 6-fold dose reductions in full-spine imaging without sacrificing image quality. Evaluations of telemedicine show outcomes equivalent or superior to traditional care in Patient-Reported Outcome Measures (PROMs) and consistently lower costs. Discussion: Major research gaps persist, particularly the limited focus on patient-centered outcomes. Methodological quality in digital health HTAs remains critically low, with inadequate integration of Patient-Reported Experience Measures (PREMs) and economic evaluations. Addressing biological variability and embedding sex and gender analysis are essential for equity and validity. Conclusion: HTA structures complex healthcare decisions beyond costs and technology metrics. Future research should strengthen evidence linking technology to patient outcomes and incorporate equity and experience dimensions.